Dynamic changes in serum steroid hormone during the first trimester of pregnancy between infertile women conceiving with and without hormone replacement therapy. Issue 10 (October 2021) - Ito, Ayumu; Katagiri, Yukiko; Fukuda, Yusuke; Morita, Mineto
Abstract: Objective: Recent advances in cancer treatment and reproductive medicine have made the post-treatment quality of life an important concern for cancer survivors. We aimed to evaluate the safety of sex hormone (estradiol and progesterone) replacement therapy (HRT) in women who conceived by assisted reproductive technology (ART) with hormone receptor-positive breast cancer. Methods: We measured serum E2 and P4 levels at 4–10 weeks of gestation in women who conceived naturally or after timed intercourse or intrauterine insemination for infertility without HRT for luteal support (non-HR group; n = 135). We conducted a retrospective comparison of the values from the non-HR group with those of women who conceived by ART with HRT for infertility (HR group; n = 75). Results: Serum E2 levels were significantly higher in the non-HR group than in the HR group at 5, 6, and 8 weeks of gestation. Similarly, serum P4 levels were significantly higher in the non-HR group than in the HR group at 4, 5, and 6 weeks of gestation. Conclusions: This study suggests that in cancer reproductive medicine for hormone-dependent breast cancer survivors, HRT administered during the first trimester of a pregnancy after primary disease treatment may not increase the sex hormone levels to levels above those seen in spontaneous pregnancy. Abstract : Breast cancer; Hormone receptor-positive; Cancer survivor; Oncofertility; Fertility preservation; Adolescent and young adult; HRT; Frozen-thawed embryo transfer; Estrogen; Progesterone.